The Conversation Hub: Explaining Students’ Transition from Surface to Deep Mathematics Learning - Bora Phan; Gema Hista Medika (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
The transition from surface-oriented learning to deep learning remains a significant challenge in mathematics education, particularly in understanding how students develop deeper conceptual engagement through authentic classroom experiences. This study aimed to develop a substantive theoretical explanation of how Grade 12 students transition from surface-oriented learning toward deep learning in mathematics classrooms. A Constructivist Grounded Theory approach was employed, using semi-structured interviews to collect data from Grade 12 students. Data were analyzed through iterative coding procedures, including initial, focused, and theoretical coding, to identify recurring categories and generate an emerging theoretical model. The findings revealed that students' progression toward deep learning was facilitated through continuous mathematical conversations, enabling them to connect prior knowledge, collaboratively construct conceptual understanding, reflect on mathematical reasoning, and apply knowledge in meaningful contexts. These interconnected learning experiences culminated in the emergence of the Conversation Hub, identified as the core category explaining students' transition from surface-oriented learning to deep learning. This study contributes to mathematics education by providing a substantive theoretical explanation of students' learning processes and offers a practical framework for designing mathematics classrooms that foster collaborative dialogue, conceptual understanding, and meaningful learning..